(3GdCMGOjK GdeSdSdI HGdCSGfjO GdYhGdis - (3eMeO SYOj Hf MeRI GdMSjfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY ebGe Cgd GdMOjK hLYdge dNdbI CFeI hbGOI hUMM fHGJge aMSfJ CNdGbge s
(3BNQgG (B:s
(3SHMGf QHc QH GdYRI YeG jUahf , hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs